182k views
0 votes
Convert to slope-intercept from: y-3=6(x-5)

2 Answers

4 votes

Hey there! I'm happy to help!

Slope intercept form is y=mx+b. So, the first thing we want to do is isolate y on side of the equation.

y-3=6(x-5)

We use distributive property to undo parentheses.

y=3=6x-30

We add 3 to both sides.

y=6x-27

Now, this in slope intercept form.

Have a wonderful day! :D

User KJParker
by
4.7k points
2 votes

Answer:

y = 6x -27

Explanation:

y-3=6(x-5)

Distribute

y-3 = 6x-30

Add 3 to each side

y-3+3 = 6x-30+3

y = 6x -27

This is in slope intercept form y=mx+b where m is the slope and b is the y intercept

User Pratik Shelar
by
5.5k points